Deep Brain Stimulation Treating Dystonia: A Systematic Review of Targets, Body Distributions and Etiology Classifications - Fan, Houyou; Zheng, Zijian; Yin, Zixiao; Zhang, Jianguo; Lu, Guohui (Frontiers in Human Neuroscience, 2021)
Background: Deep brain stimulation (DBS) is a typical intervention treating drug-refractory dystonia. Currently, the selection of the better target, the GPi or STN, is debatable. The outcomes of DBS treating dystonia classified by body distribution and etiology is also a popular question. Objective: To comprehensively compare the efficacy, quality of life, mood and adverse effects (AEs) of GPi-DBS versus STN-DBS in dystonia as well as in specific types of dystonia classified by body distribution and etiology. Methods: PubMed, Embase, the Cochrane Library, and Google Scholar were searched to identify studies of GPi-DBS and STN-DBS in populations with dystonia. The efficacy, quality of life, mood and adverse effects were quantitatively compared. Meta-regression analyses were also performed. This analysis has been registered in PROSPERO under the number CRD42020146145. Results: 35 studies were included in the main analysis, in which 319 patients underwent GPI-DBS and 113 patients underwent STN-DBS. The average follow-up duration was 12.48 months (range, 3-49 months). The two groups were equivalent in terms of efficacy, quality of life, mood and occurrence of AEs. The focal group demonstrated significantly better disability symptom improvement (P=0.012) but showed less SF-36 enhancement than the segmental group (P<0.001). The primary groups exhibited significantly better movement and disability symptom improvements than the secondary nonhereditary group (P<0.005), which demonstrated only disability symptom improvement compared with the secondary hereditary group (P<0.005). The primary hereditary and idiopathic groups had a significantly lower frequency of AEs than the secondary nonhereditary group (P<0.005). The correlation between disability symptom improvement and movement symptom improvement was also significant (P<0.05). Conclusions: GPi-DBS and STN-DBS were both safe and resulted in excellent improvement in efficacy and quality of life in patients with dystonia. Compared with patients with segmental dystonia, patients with focal dystonia demonstrated better improvement in dystonia symptoms but less enhancement of quality of life. Those with primary dystonia had a better response to DBS in terms of efficacy than those with secondary dystonia. Patients who exhibit a significant improvement in movement symptoms might also exhibit excellent improvement in disability symptoms.